SPIRITUAL CARE FOR THE ELDERLY: OFFERING THE OPPORTUNITY TO TALK ABOUT DEATH - BRANDT, Pierre-Yves; DANDAROVA ROBERT, Zhargalma; LAUBSCHER, Karine (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
To speak of the Romanian village today is to consider a reality of life populated more and more by elderly people and children whose parents work outside the home, in town, or even abroad. The quality of life of the elderly remaining in the village is, in this context, a major concern for the political authorities and religious leaders. Indeed, many studies have shown that taking into account the religious and spiritual dimension contributes to the well-being of seniors. Recent research in Switzerland has highlighted the fact that many elderly people who live in senior care facilities are interested in talking about death with someone they trust. This trusted person is not necessarily the priest or chaplain. For many residents, this role is given to someone within the elderly person’s network of family and friends (spouse, daughter, niece, close friend, etc.). What happens when this network is empty and the elderly person is more isolated? We propose to think about how these observations can be transposed into a practice of spiritual care adapted to the context of the Romanian village.